2004
DOI: 10.1038/sj.bjc.6601896
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of failure in gastric carcinoma after D2 gastrectomy and chemoradiotherapy: a radiation oncologist's view

Abstract: The risk of locoregional recurrence in resected gastric adenocarcinoma is high, but the benefit of adjuvant treatment remains controversial. In particular, after extended lymph node dissection, the role of radiotherapy is questionable. Since 1995, we started a clinical protocol of adjuvant chemoradiotherapy after D2 gastrectomy and analysed the patterns of failure for 291 patients. Adjuvant chemotherapy consisted of five cycles of fluorouracil and leucovorin, and concurrent radiotherapy was given with 4500 cGy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 23 publications
5
50
0
5
Order By: Relevance
“…The radical therapy of gastric carcinoma mainly relies on surgical resection; however, local recurrence and distant metastasis may still occur, even in patients who have undergone complete surgical resection (3)(4)(5). Among patients with failed surgical intervention, ~90% experienced local recurrence, which led to death in ~80% of these patients, particularly those with serosal invasion or lymphatic metastasis (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The radical therapy of gastric carcinoma mainly relies on surgical resection; however, local recurrence and distant metastasis may still occur, even in patients who have undergone complete surgical resection (3)(4)(5). Among patients with failed surgical intervention, ~90% experienced local recurrence, which led to death in ~80% of these patients, particularly those with serosal invasion or lymphatic metastasis (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…However, even after complete resection and adequate D2 lymphadenectomy, high rates of locoregional recurrence continue to be reported [1][2][3][4][5][6]. Several approaches have been tried to improve the clinical outcome of resectable gastric cancer, including adjuvant chemotherapy (CT), concurrent radiochemotherapy (cRCT), and perioperative chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, many oncologists questioned whether the survival benefit may have resulted from the insufficiency of the surgery since only 10% of the patients in the trial received D2 resection and 54% of the patients received less than D1 resection. A Korean study achieved a positive result similar to the INT0116 trial, and it showed that adjuvant chemoradiotherapy decreased local recurrence and improved survival only for patients with t3-4n0M0 and t1-4n+ disease, but not for patients with t1-2n0M0 disease (30).…”
Section: Adjuvant Chemotherapy or Chemoradiotherapy After Surgerymentioning
confidence: 88%